A case of very aggressive maxilar osteosarcome in a young subject - Ulrich Opoko; Ayoub Sabr; Fidélia Nihad Da Silva; Mohamed Raiteb; Meriem Regragui; Faiçal Slimani (Elsevier, 2021)
Introduction: Osteosarcomas are potentially lethal malignant bone tumours, more commonly found in the long bones than in the maxillofacial region. Sarcomas are known for their difficult diagnosis, rapid progression and poor prognosis. Observation: We present a case of osteosarcoma of the maxilla in a young subject who was treated and followed for 2 years. The diagnosis and the start of treatment were made 12 months after the first symptoms. The definitive diagnosis was made by pathological examination of the resection specimen. The treatment required several therapeutic means combining surgery, chemotherapy and radiotherapy. Discussion: The treatment of osteosarcoma most often combines surgery, chemotherapy and radiotherapy; however, surgery remains the treatment of choice. Chemotherapy has significantly improved the prognosis of long bone osteosarcomas, however its role in the treatment of maxillary osteosarcomas remains controversial. It is currently accepted that protocols combining neo-adjuvant chemotherapy with adjuvant chemotherapy provide better results than adjuvant chemotherapy alone. Analysis of the surgical specimen provides an early assessment of the response to chemotherapy and determines the adjuvant therapy. The prognosis of osteosarcoma depends on several parameters, including the latency period between the first symptoms and therapeutic management; the size of the tumour; its location, with maxillary locations having a poorer prognosis than mandibular locations; the quality of tumour removal; whether or not there is a response to neo-adjuvant chemotherapy; whether or not there are metastases and the degree of differentiation.